Enhancing Accessibility of Physical Activity During Pregnancy: A Pilot Study on Women's Experiences With Integrating Yoga Into Group Prenatal Care. (2nd April 2019) - Kinser, Patricia; Jallo, Nancy; Thacker, Leroy; Aubry, Christine; Masho, Saba
Introduction: Health guidelines suggest that pregnant women should participate in daily physical activity, yet rarely do they meet these guidelines. Means to enhance accessibility of physical activity for pregnant women are required, and yoga has been suggested as a possible method to enhance women's sense of confidence and competence with physical activity. In this pilot study, our primary aim is to evaluate pregnant women's perceptions about their lived experience of an intervention which integrates a low-intensity form of physical activity, yoga, into prenatal care; our secondary aim is to evaluate changes in participants' self-efficacy for physical activity and time spent in physical activity over time. Methods: Held in an outpatient obstetrics department of an urban hospital system in the United States, this pilot study enrolled 16 pregnant women to participate in the intervention throughout their pregnancy. We explored participants' lived experience of the intervention using qualitative methods (phenomenology). Means, variances, and covariances were calculated for the 2 measures (self-efficacy and time spent in physical activity) over the intervention period. Results: Qualitative findings from focus groups suggest that it is acceptable for prenatal yoga to be integrated into group prenatal care classes and women reported increased confidence with physical activity during pregnancy. Participants did not consider the intervention to fit within the traditional definition of exercise. Women reported increased amounts of time spent in physical activity from baseline to the end of pregnancy, but there were no statistically significant changes in self-efficacy over time. Discussion: The integration of gentle physical activity into the group prenatal care model warrants further attention for potential benefits with regard to maternal physical and mental wellness.